#TITLE_ALTERNATIVE# - SYUFYAN (NIM 12206087); Pembimbing: Pembimbing: Prof. Dr. Ir. Doddy Abdassah, HIDAYATUS
Coalbed Methane (CBM) is unconventional gas which is play important role in energy source supply in Indonesia. The main difference between CBM and conventional gas is about gas storage mechanism and production processes. In conventional gas, the gas is stored in pores as free gas in reservoir. While in CBM, the gas was embeded in primary porosity (micropore). The gas is adsorbed in to coal surface. The production process was also different. As the gas pressure decreasing, the gas would detached from coal surface. The detached gas then flow in to cleat by diffusion. The gas flowing along from cleat to the wellbore obeying Darcy Law. Therefore, production profile in this process would be different compared with other gas depletion process. In this paper, author perform production profile prediction of gas and water in coalbed methane reservoir using King and Seidle methods.